Natural disaster crises in Bulgaria in the period 2010 – 2020 - Berberova, Ralitza; Kostova, Bilyana (Annual of Natural Sciences Department, 2025)
Results of the interpretation of official statistical data on natural disaster crises in Bulgaria for the period from 2010 to 2020 are presented. The study of natural hazards and the monitoring of the crises caused by them are important activities in terms of prevention and in the context of sustainable development, due to their impact on the economy, the environment and the people’s quality of life. Such crises are registered in our country every year. The results show that more than half of the occurring natural disaster crises are due to floods, and for the occurrence of some of them, the anthropogenic factor must be taken into account. A downward trend in the occurrence of natural disaster crises has been identified, with a significant peak in registered crises in 2012.